دراسة مقارنة بين أنواع من ( الراتنج المركّب ) الكمبوزيت من حيث القساوة - حداد منذر (Latakia University Journal -Medical Sciences Series, 2016)
تألّفت عيّنة البحث من 30 قالب من الراتنج المركّب ، قسّمت إلى ثلاث مجموعات متساوية ، 10 من الراتنج المركب Z-250 من شركة ESPE 3M ، 10 من الراتنج المركب Supreme من شركة ESPE 3M، 10 من الراتنج المركب Quixfil من شركة Dentsply تم اختبار رقم القساوة لكل عينة على حدى، و كان الهدف من ذلك بيان دور تركيب الراتنج المركب في تحديد مقدار قيمة هذه القساوة وذلك من خلال الفروقات في رقم هذه القساوة ودور القساوة في تحديد الخواص الميكانيكية لترميمات الراتنج المركب كون هذه الخاصية هامة لفهم الخواص الميكانيكية لكثير من المواد الترميمية، و النتيجة أن هناك دلالة إحصائية ما بين راتنجي الـ Quixfil و الـ Z-250 من جهة وراتنج الـ Supreme من جهة أخرى . The research project sample consisted of 30 blocks of composite resin , these blocks where divided into three equal groups , 10 of composite resin Z-250 from 3M ESPE Company , 10 of the composite resin Supreme from 3M ESPE Company ,10 of the composite resin Quixfil of Dentsply company, and has been testing the hardness Number, each sample individually. The aim of the previous procedures was to show the role of composite resin structure in determining the hardness number Through differences in the hardness number and the role of this hardness determining the mechanical properties for composite resin restorations cause of the importance of this property to understand the mechanical properties for a lot of restorative materials. And the result is that there is a statistically significant between the resin Quixfil and the Z-250 on the one hand and the Supreme resin on the other hand.